NURTURING INTERLANGUAGE PRAGMATIC COMPETENCE THROUGH DYNAMIC ASSESSMENT - Prastikawati, Entika Fani; Lestari, Maria Yosephin Widarti; Asropah, Asropah (Journal of English Education and Linguistics, 2024)
This study investigates the impact of peer-Dynamic Assessment (peer-DA) on the development of interlanguage pragmatic (ILP) competence among Indonesian EFL learners. While pragmatic competence is crucial for appropriate language use, systematic assessment approaches remain limited in the Indonesian EFL context, particularly regarding the integration of instruction and assessment. Through a true experimental design, 43 upper-intermediate EFL learners were randomly assigned to experimental (n=22) and control (n=21) groups. The experimental group received peer-DA instruction emphasizing collaborative scaffolding and reciprocal mediation, while the control group received traditional non-DA instruction. Data collection utilized the Key English Test (KET) for homogenization and dual multiple-choice ILP assessments for pre-and post-testing. Statistical analysis through independent samples t-tests revealed no significant differences between groups in pre-test scores (t(35)=2.92, p>.05). However, post-test results demonstrated significantly higher ILP competence in the experimental group (M=14.79, SD=3.14) compared to the control group (M=8.11, SD=2.78; t(35)=4.47, p<.05). These findings suggest that peer-DA effectively enhances Indonesian EFL learners' pragmatic competence, offering valuable implications for integrating assessment and instruction in EFL pragmatic development.